OWE-009 Developing a core outcome set for fistulising perianal crohn's disease. (8th June 2018) - Sahnan, Kapil; Tozer, Phil; Adegbola, Samuel; Lee, Matthew; Heywood, Nick; McNair, Angus; Hind, Daniel; Yassin, Nuha; Lobo, Alan; Brown, Steve; Sebastian, Shaji; Phillips, Robin; et al.
Abstract : Introduction: Lack of standardised outcomes hampers effective analysis and comparison of data when comparing treatments in fistulising perianal Crohn's disease (pCD). Development of a standardised set of outcomes would resolve these issues. This study provides the definitive core outcome set (COS) for fistulising pCD. Methods: Candidate outcomes were generated through a systematic review and patient interviews. Consensus was established via a three-round Delphi process using a nine-point Likert scale based upon how important they felt it was in determining treatment success culminating in a final consensus meeting. Stakeholders were recruited nationally and grouped into three panels (Surgeons and Radiologists, Gastroenterologists and IBD specialist nurses, Patients). Participants received feedback from their panel (in the second round) and all participants (in the third round) to allow refinement of their scores. Results: A total of 295 outcomes were identified from systematic reviews and interviews that were categorised into 92 domains. 187 stakeholders (response rate 78.5%) prioritised 49 outcomes through a three-round Delphi study. The final consensus meeting of 41 experts and patients generated agreement on an eight domain COS. The COS comprised three patient-reported outcome domains (quality of life, incontinence and a combined score of patient priorities) and five clinician-reported outcome domains (perianal disease activity, development of new perianal abscess/sepsis, new/recurrent fistula, unplanned surgery and faecal diversion). Conclusion: A fistulising pCD COS has been produced by all key stakeholders. Application of the COS will reduce heterogeneity in outcome reporting, thereby facilitating more meaningful comparisons between treatments, data synthesis and ultimately benefit patient care.